Hubungan Perilaku Orang Tua Dalam Pemilihan Makanan Bergizi Dengan Status Gizi anak Pada Anak Usia Pra Sekolah - Al syafarinoo; Lilla Maria; Rahmawati Maulidia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2020)
Parents act has an important role in fulfilling the children’s food needs to support the process of their growth and nutritional status. This research objective is to find out the correlation between the Parents capability in selecting nutritious food and nutritional status of Pre-School age children in ABA 06 Kindergarten Mergosono Kedungkandang, Malan. The design of this research is correlation with cross sectional approach. The research populations were 70 people. The determination of a purposive sampling in this research used 60 respondents. The technique of collecting the data used the questionnaires. The data were analyzed by using spearmen rank test and SPSS. The research results prove that most of the 39 (65.0%) parents have enough capability in selecting nutritious foods on the pre-school age children and almost entirely 52 (86.7%) pre school age children have good nutritional status. Test result of spearmen rank obtained; p-value = (0.000) < (0.05). It can be concluded that there is a correlation between parents’capability in selecting nutritious food and nutritional status in pre-school age children in aba 06 kindergarten Mergosono Kedungkandang, Malang. From the result of the research, it is stated that imroving the nutritional status of pre-school aged children needs a good capability of the parents in selecting nutritious food